Peranan Room Attendant Dalam Make Up Room Untuk Meningkatkan Kepuasan Tamu Di Hotel Des Indes - Martinus Hia; Triyono Arief Wahyudi (STREAMING, 2025)
This study examines the role of room attendants in performing make-up room procedures and their impact on guest satisfaction at Hotel Des Indes Menteng. Using hospitality service theory and hotel operational standards, the research explores how room attendant knowledge, technical skills, interpersonal behavior, and adherence to Standard Operating Procedures (SOPs) influence perceived room quality and guest experience. A descriptive qualitative approach was employed through six months of fieldwork (June–December 2021), including literature review, participant observation in the housekeeping department, and interviews with room attendants and supervisors. The findings indicate that accurate technical execution, consistent SOP implementation, and courteous interpersonal behavior significantly enhance guest comfort, hygiene perception, and service reliability. However, inconsistent SOP enforcement, limited chemical-handling knowledge, variable inspections, and insufficient continuous training were identified as constraints. The study recommends structured training, strengthened supervision, SOP reinforcement, and performance monitoring to improve housekeeping quality and guest satisfaction.